SISTEM INFORMASI PEMESANAN PRODUK SECARA ONLINE CAFÉ STRAWBERRY CIMAHI - Dadi Rosadi; Diah Rodiah (Jurnal Computech & Bisnis (e-Journal), 2015)
The application of software and internet has been growing rapid in this era and also web application and browser internet or intranet. E-commerce or e-business has been development and it is start by EDI (Electronic Data Interchange) has been development in International scrap.  Application software best on internet is very support to development of business it connection it effective and affection of work. Best on this analysis of the applicable system used café strawberry Cimahi, there are several problem : due to many customer so company want to increase to server them by applying digital system or used internet, also ass needed online transaction. To soft problem it must be designed the development system of ordering, by online system with develop from previous system. Keywords: Pemasaran produk, online   AbstrakAplikasi perangkat lunak dan internet telah berkembang pesat pada era ini dan juga aplikasi web dan browser internet atau intranet. E - Commerce atau e - busness developmend dan itu mulai dengan EDI (Electronic Data Interchange) telah menjadi pengembangan secara internasional. Aplikasi software terbaik di internet untuk pengembangan Bisnis itu koneksi yang efectif dan efisiensi kerja. Analisis sistem yang berlaku pada café yang digunakan oleh stroberi Cimahi, ada beberapa masalah antara lain: karena banyak pelanggan sehingga perusahaan ingin meningkatkan ke server mereka dengan menerapkan sistem digital atau menggunakan internet, selain itu juga diperlukan transaksi online. Untuk masalah tersebut itu harus merancang sistem pengembangan pemesanan sistem online dengan pengembangan dari sistem sebelumnya. Kata Kunci: Pemasaran produk, online